Business school sustainability revisited: Sustainable no more? - PETERS, Kai (Institutional Knowledge at Singapore Management University, 2023)
Kai Peters and Howard Thomas reflect on their 2011 Global Focus article, “A Sustainable Model for Business Schools”, and 2018 book, “Rethinking the Business Model of Business Schools”, and update the thoughts and developments since then.